Perancangan Visual Artwork Dengan Teknik Desain Pop Up Pada Board Game Untuk Media Pembelajaran Pencegahan Malnutrisi Untuk Usia 10 – 11 Tahun - Sutikno, Melinda Rachel; Prestiliano, Jasson; Pratiwi, Peni; Setiawan, Arie (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2023)
Lack of fruit and vegetable intake can cause malnutrition in the body because fruits and vegetables contain many important vitamins for body health. Children are reluctant to eat fruits and vegetables due to lack of awareness of healthy eating patterns. In this problem, children need to be given education, namely board game learning media for the prevention of malnutrition entitled "fruitvege missions". This design uses a combined method, namely "mixed method" to obtain more robust and comprehensive data. In designing, it also takes an interesting and unique visual artwork, namely pop up because it is three-dimensional and interesting for children. The things obtained in this board game improve the quality of children's learning and help children be aware of health from an early age.